STUDI KASUS PENINGKATAN KUALITAS MENGGUNAKAN METODE SIX SIGMA DAN FMEA PADA PERUSAHAAN CARBON ROD BATERAI - Setiawan, Yesaya Hansel; Saryatmo, Mohammad Agung; Sukania, I Wayan (Jurnal Mitra Teknik Industri, 2025)
This research was conducted at PT. XYZ, a company that manufactures carbon rods, by applying the Six Sigma method using the DMAIC and FMEA approaches. The data is taken from production results during the period April 2024 to March 2025, which shows an average defect rate of 4.9%. The initial stage of the research begins with identifying critical to quality (CTQ), which is the need for high-quality carbon rod products that are able to meet customer demand consistently. Process mapping and quality performance calculation were carried out using the Six Sigma method, which resulted in a DPMO value of 6,997 and a sigma level of 3.96. These results show that the production process needs to be improved. The main causes of defects are analyzed using a cause-and-effect diagram based on five types of defects, namely fracture, chipping, cracking, perforation, and tilted position, which are influenced by human factors, machines, methods, and working environments. through FMEA analysis, it was found that the causes of failure with the highest FRPN values were found, such as engine speed that was too high, cleanliness of machinery and other production equipment that is not observed or neglected, and errors in engine adjustment. Proposed improvements are carried out with a Kaizen approach through 5S and five M-checklists, and are implemented in the form of SOPs and checksheets. As a result, the defect rate was successfully reduced from 4.9% to 3.5%.